Network Infrastructure Design and Website Management of Perumdam Tirta Bengkayang - Azriel Christian Nurcahyo; Agustinus Rudatyo Himamunanto; Listra Firgia (Institut Teknologi Nasional, Bandung, 2022)
The management and optimization of IT infrastructure are vital for the Regional-Owned Enterprise Agency, Perumdam Titra Bengkayang, considering the number of connections on 2021 was 10.100 SR and the number continues to grow. This causes the need to improve services in the field of information technology, especially facilities and infrastructure for information disclosure of public bodies involving facilities such as network infrastructure and websites as well as online payment systems. Since the change of director and of name from PDAM to Perumdam Tirta Bengkayang, it is stated in the five year strategic plan to change the status of information disclosure from the black zone in 2019 at least to yellow for 2020-2022 and blue or green for 2023-2024. Through this activity, the design of a network system among the branches of the Perumdam Tirta Bengkayang office and website management to facilitate monitoring and evaluation of information disclosure for public agencies were done. This activity resulted in a network design based on inter-branch networks for future improvements and website management based on wordpress CMS.